(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1862)
This author tracks the history of the Hospital of St Martha in Aberdour from the earliest mention of the ’Pilgrim’s Well’, a holy well believed to heal the sick, through the Earl of Morton granting the surrounding acreage to the church and finally the appointment of four of the sisters of St Francis to run the hospital. The circumstances of the return of the land is also noted and the author concludes with some comments about the location and use of the ’Pilgrim’s Well’.